Globe locust (Robinia pseudoacacia var. umbraculifera D.C.): a potential forage species? - Dini-Papanastasi O. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Globe locust (Robinia pseudoacacia var. umbraculifera D.C.), a small leguminous tree, is one of the several botanical varieties of black locust (Robinia pseudoacacia L.). It has a dense, globe-shaped crown, and it is often used - grafted on a black locust rootstock - for ornamental purposes. It is thornless and rarely flowers. This variety was studied in terms of forage production and quality along with clones and half-sib families of the black locust variety monophylla and common black locust as a control, in the farm of the Forest Research Institute, NE of Thessaloniki, in Greece . More specifically, ramets of globe locust produced by rooted stem cuttings were tested for three consecutive years (1994-96) and at the end of each growing period the height, the above ground biomass and crude protein (CP) content of leaves were measured.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)